Sacred hearts : a novel - Dunant, Sarah (New York : Random House, 2009)
The year is 1570, and in the convent of Santa Caterina, in the Italian city of Ferrara, noblewomen find space to pursue their lives under God's protection. But any community, however smoothly run, suffers tremors when it takes in someone by force. And the arrival of Santa Caterina's new novice sets in motion a chain of events that will shake the convent to its core.
"Originally published in the United Kingdom by Virago Press, an imprint of the Little, Brown Book Group, London"--T.p. verso.
Includes bibliography: p. [413]-415.
edited hb 2015-06-16
Keywords: Convents -- Italy -- Fiction; Nuns -- Italy -- Fiction; Women -- Italy -- Social conditions -- 16th century -- Fiction; Ferrara (Italy) -- Fiction; Historical fiction